2006
DOI: 10.2117/psysoc.2006.178
|View full text |Cite
|
Sign up to set email alerts
|

Children's Category Structure and False Memories

Abstract: Extensive previous research has focused on the development of children's conceptual organization and its effects on children's veridical memory. The present research investigated whether the structure of children's category knowledge also affected their false memories using categorical lists in the DRM paradigm, a listlearning method commonly used in false memory research. In Experiment 1, the effects of graded category structure were examined with both third and sixth graders by accessing false memories for u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Chen (1978) following Nelson (1974) found that between five and eight years of age Mandarinspeaking children's concepts of solid objects increase in both size and hierarchical organization. Chiang and Chiu (2006) offer evidence that Mandarin children have categories organized hierarchically by 10 years of age. To our knowl edge, only two published studies have examined the development of shape-based 1 categorization in Mandarin speakers: Li et al (2009) andImai et al (2010).…”
Section: Categorization Of Solid Objectsmentioning
confidence: 96%
“…Chen (1978) following Nelson (1974) found that between five and eight years of age Mandarinspeaking children's concepts of solid objects increase in both size and hierarchical organization. Chiang and Chiu (2006) offer evidence that Mandarin children have categories organized hierarchically by 10 years of age. To our knowl edge, only two published studies have examined the development of shape-based 1 categorization in Mandarin speakers: Li et al (2009) andImai et al (2010).…”
Section: Categorization Of Solid Objectsmentioning
confidence: 96%
“…Actually, relying exclusively on the concept of gist, it would be difficult to explain such results. As was pointed out earlier (Chiang & Chiu, 2006), fuzzy-trace theory is unspecific about which item*dominant basic or category label* is the best representation of a categorised list. Gist-based explanations are problematic, especially if one accepts that the category name, corresponding to the theme of the list, is considered to be the gist representation.…”
Section: Discussionmentioning
confidence: 98%
“…Two recent studies, one with adults (Park et al, 2005) and the other with older children (Chiang & Chiu, 2006), showed that when the critical lure is from another level of categorisation of the list items, false memories are rarely produced. Adults and older children (around 10 years old) usually do not falsely recognise names of categories 1 It is important to note that our own view differs from the associative activation theory (AAT) by Howe (2005Howe ( , 2006a in the sense that his theory is not considered a dual-process theory.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations